Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan di Masa Pandemi Covid – 19 Studi Kasus PT Telekomunikasi Seluler (GraPARI) Kota Makassar - Septari Zandrah, Fadilah; Adi; Jusri (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2021)
This study aims to test and analyze the effect of work motivation and work discipline on employee performance at PT Telekomunikasi Seluler (GraPARI) Makassar. The sample used was 56 respondents from the total population. The analysis method used is descriptive analysis and statistical analysis. The statistical method uses Multiple Linear Regression Analysis, with t statistical test hypothesis testing. The results of the analysis show that work motivation has a positive and significant effect on employee performance where t count is greater than t table (3.614> 2.00575) and discipline has a positive and significant effect on employee performance where the t value is greater than t table (2.177> 2.00575).